O sofrimento de imigrantes: um estudo clínico sobre os efeitos do desenraizamento no self - Maalouf, Jorge Fouad (2005)
This study will both investigate and contemplate immigrants, unrootedness and its implications for an immigrant s self from the clinical point of view. As a clinical psychologist, the researcher is interested in investigating the manifestation of suffering in immigrants as well as the devices those individuals may resort to in an attempt to deal with the said feelings. It is a general assumption that unrootedness is a kind of ailment which may leave deep scars on the feelings both immigrants and their descendants have of themselves. The researcher has used the life history interview method to analyze and discuss the reports given by five immigrants. In order to make remarks about the immigrants testimonials, the researcher starts his studies based on Winnicott s psychoanalytic theory of the maturational process, followed by the contributions of Safra (1999 2004), the notion of unrootedness by Simone Weil, and the concepts of spirituality and hyletics by Edith Stein. Six factors have shown to be both important and common in the interviewees experiences: home, language, spirituality, friendship, depression and a sense of strangeness. With the present investigation, the researcher tries to focus on the conditions that lead to rootedness. The possibility to testify to an interviewee s personal course of life and to create a narrative of their life history has shown to be a meaningful experience that generates a sense of rootedness